1994
DOI: 10.1118/1.597253
|View full text |Cite
|
Sign up to set email alerts
|

A cone beam SPECT reconstruction algorithm with a displaced center of rotation

Abstract: A filtered backprojection (FBP) algorithm is derived based on Feldkamp's FBP algorithm for a cone beam geometry that has a displaced center of rotation. In cone beam single photon emission computed tomography (CB-SPECT) the center of rotation displacement can degrade the reconstructed images. The center of rotation displacement of interest is mechanical shift, which is the displacement of the midplane of the cone beam collimator off the rotation center. Mechanical shift is characterized by two orthogonal compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Inaccurate knowledge of the position of the principal ray can lead to artifacts in reconstructed images. [9][10][11] Principal ray mispositioning from the ideal situation indicated above is not uncommon and has been observed in these previous studies.…”
Section: Introductionsupporting
confidence: 57%
“…Inaccurate knowledge of the position of the principal ray can lead to artifacts in reconstructed images. [9][10][11] Principal ray mispositioning from the ideal situation indicated above is not uncommon and has been observed in these previous studies.…”
Section: Introductionsupporting
confidence: 57%
“…1,7,14 It was reported that 3D images obtained using the cone-beam scanners are inevitably distorted away from the central slice as the single-orbit cone beam geometry does not provide a complete data set. 9,13 These distortions and the associated loss of spatial resolution are particularly evident in samples containing plate-shaped structures, and are minimized by reducing the cone-beam angle. 5,9,13 However, a smaller cone-beam angle has often been found to be associated with lesser number of scanning fields and lower resolution.…”
Section: Introductionmentioning
confidence: 99%
“…9,13 These distortions and the associated loss of spatial resolution are particularly evident in samples containing plate-shaped structures, and are minimized by reducing the cone-beam angle. 5,9,13 However, a smaller cone-beam angle has often been found to be associated with lesser number of scanning fields and lower resolution. This was attributed to the limitation of the distances between the object, X-ray tube, and detectors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations